2022
DOI: 10.3390/f13101625
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Effects of Green Experiences in a Virtual Environment: A Systematic Review

Abstract: As mental health issues increase worldwide, nature-based experiences are being recognized as alternative treatments for improving health and well-being. Increasing urbanization precludes many people from accessing green spaces owing to time or physical limitations. Therefore, opportunities to connect with nature through virtual technology is being encouraged. We conducted a systematic review of studies on the psychological effects of experiencing nature using virtual technology. We searched the academic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 76 publications
1
16
0
1
Order By: Relevance
“…Across the studies included in our systematic review, we observed a recovery effect from stress after the exposure to VR nature, in both objective and subjective measures. This result is in line with the scientific literature concerning the beneficial effects of physical nature (Shuda et al, 2020), VR (Riches et al, 2021), and natural scenarios through VR (Lee et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Across the studies included in our systematic review, we observed a recovery effect from stress after the exposure to VR nature, in both objective and subjective measures. This result is in line with the scientific literature concerning the beneficial effects of physical nature (Shuda et al, 2020), VR (Riches et al, 2021), and natural scenarios through VR (Lee et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Different systematic reviews exist on the relaxation effects of nature through VR (Frost et al, 2022; Lee et al, 2022), but no systematic reviews were retrieved on the recovery effects of nature after inducing acute stress.…”
mentioning
confidence: 99%
“…Previous studies have mostly employed self-report questionnaires ( Lee et al, 2022 ), which relied on subjects’ perceptions of the current state at the conscious level. With this approach, however, there was inevitable “subjectivity” and insufficient objectivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, knowledge gaps remain regarding the effects of exposure duration on health benefits. A systematic review revealed that virtual nature interventions lasting more than 10 min produced more consistent effects than those of a shorter duration [110]. However, the optimal viewing duration may vary across media formats.…”
Section: Dose and Durationmentioning
confidence: 99%